Anopheles (Kerteszia) lepidotus (Diptera: Culicidae), not the malaria vector we thought it was: Revised male and female morphology; larva, pupa, and male genitalia characters; and molecular verification - Harrison, Bruce A.; Ruiz-Lopez, Freddy; Falero, Guillermo Calderon; Savage, Harry M.; Pecor, James E.; Wilkerson, Richard C. (Zootaxa, 2012)
The name Anopheles (Kerteszia) lepidotus Zavortink, commonly used for an important malaria vector in the eastern cor-dillera of the Andes, is here corrected to An. pholidotus Zavortink. We discovered that An. (Ker.) specimens from Peru,and reared-associated specimens from Ecuador, had unambiguous habitus characters that matched those on the male ho-lotype of An. lepidotus. However, the specimens do not exhibit characters of the female allotype and female paratypes ofAn. lepidotus, which are actually An. pholidotus. Our specimens are the first correctly associated females of An. lepidotus,which allow us to provide a new morphological interpretation for the adult habitus of this species. This finding is alsocorroborated by molecular data from a portion of the Cytochrome Oxidase I (COI) gene and ribosomal DNA Internal Tran-scribed Spacer 2 (rDNA ITS2). The pupal stage of An. lepidotus is described for the first time, and additional larval char-acters are also noted. Diagnostic morphological characters for the adult, pupal, and larval stages of An. pholidotus areprovided to separate the two species. All stages of An. lepidotus are easily separated from other currently known speciesin subgenus Kerteszia and a new key to the females of An. (Kerteszia) is given. Previously published distribution, bionomics, and medical significance data are corrected and enhanced.